РУССКАЯ ЛИНГВИСТИЧЕСКАЯ ТЕРМИНОЛОГИЯ: ПРОБЛЕМА ЗАИМСТВОВАНИЯ - ИВАНОВА, ГАЛИНА (Studia Rossica Posnaniensia, 2006)
The article is devoted to the ways of borrowing the terminological vocabulary by the Russian language in the field of linguistics. Special attention is paid to foreign loan words - Greek-Latin and West-European, the causes of their origin in the system of Russian linguistic terminology. Assimilation processes of foreign language terms resulting in their graphic, spelling, phonetic and grammar variation are investigated. Attention is paid to the predominance of English borrowings in the Russian terminology. It is concluded that at present the metalanguage in linguistics is at the stage of formation. It is necessary to unify the linguistic terminology.